2010
DOI: 10.3109/0886022x.2010.494799
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical characteristics between automated peritoneal dialysis and continuous ambulatory peritoneal dialysis: a 2-year single-center observational study

Abstract: Aims: To date, there is convincing evidence for the preservation of residual renal function (RRF) in peritoneal dialysis (PD) patients; however, substantially variable data exist on the incidence rate of infectious complications and the decline of RRF for automated peritoneal dialysis (APD) and continuous ambulatory peritoneal dialysis (CAPD). The purpose of our study was to investigate the relative merits or demerits of APD compared with CAPD. Methods: From November 1998 to November 2007, we retrospectively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In addition, we did not find that PD sub-modality was a risk factor for loss of RKF in the first year of PD. This agrees with most (23,29), but not all (30-32), studies. The use of icodextrin also did not influence RKF.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we did not find that PD sub-modality was a risk factor for loss of RKF in the first year of PD. This agrees with most (23,29), but not all (30-32), studies. The use of icodextrin also did not influence RKF.…”
Section: Discussionsupporting
confidence: 92%
“…(2003) [ 36 ] 6-year prospective Incident 134 CAPD, 12 APD No Rodriguez-Carmona (2004) [ 62 ] 1-year prospective Incident 53 CAPD, 51 APD Yes Hazard ratio of APD versus CAPD = −1.2 (−2.25 to −0.15, P = 0.02) Rabindranath (2007) [ 63 ] Systematic review of 3 RCT 49 PD subjects No Liao (2009) [ 27 ] 10-year retrospective Incident 188 CAPD, 82 APD No Su et al . (2010) [ 64 ] 9-year retrospective Prevalent 140 CAPD, 32 APD No Cnossen et al . (2010) [ 55 ] 7-year retrospective Incident 179 CAPD, 441 APD No Balasubramanian et al .…”
Section: Strategies For Preserving Rrf In Patients With Progressive Cmentioning
confidence: 99%
“…In China, it is important to know whether the increased cost of APD is justified by improved outcomes. The weight of evidence suggests that APD has similar effects to continuous ambulatory PD (CAPD) in terms of residual renal function (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and either lower (2,(18)(19)(20)(21)(22)(23)(24) or similar (17,(25)(26)(27)(28)) rates of peritonitis. Older studies have mostly shown similar allcause mortality (2,7,25,(29)(30)(31)(32)(33).…”
mentioning
confidence: 99%